THE NETWORKS FOR DEGRADATION AND PREACARIZATION OF LABOR IN THE SUGARCANE HYDROAGRICULTURAL IN THE ADMINISTRATIVE REGION OF PRESIDENTE PRUDENTE (SP) - Nascimento Ferreira, Gabriel Vitor [UNESP]; Bento, Fredi dos Santos [UNESP]; Thomaz Junior, Antonio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2021)
The technological transition underway in sugarcane hydroagricultural in the Administrative Region of Presidente Prudente, as part of the productive restructuring of capital, it materializes through intense mechanization of cutting and planting of sugarcane and the prevalence of the chemical-dependent model. The consequences of this process on workers 'and collective health, on exposure to risks, on workers' illnesses. Thus, in line with our research at the master's level, we intend to reveal the networks of degradation and precarious labor present in the territory of Pontal do Paranapanema and more comprehensively in the Administrative Region of Presidente Prudente, in order to understand the bonds that are formed between workers and between sugar cane agro-industries, as well as the networks projected in the territory by the personifications of sugarcane agro-industrial capital in a scalar way.
Keywords: Occupational health; health-disease process; network; territory; labor degradation